A Convenient and Label-Free Colorimetric Detection for L-Histidine Based on Inhibition of Oxidation of 3,3′,5,5′-Tetramethylbenzidine-H2O2 System Triggered by Copper Ions - Zhang, Zhikun; Zhao, Wenmeng; Hu, Cuixia; Cao, Yapeng; Liu, Yumin; Liu, Qingju (Frontiers in Chemistry, 2021)
L-Histidine (L-His) is an essential amino acid, which is used to synthesize proteins and enzymes. The concentration of L-His in the body is controlled to regulate tissue growth and repair of tissues. In this study, a rapid and sensitive method was developed for colorimetric L-his detection using Cu2+ ions to inhibit the oxidation of 3,3’,5,5’-tetramethylbenzidine (TMB)-H2O2 system. H2O2 can oxidize TMB to oxTMB in the presence of copper, and the change in color from colorless (TMB) to blue (oxTMB) is similar to that observed in the presence of peroxidase. However, because the imidazole ring and carboxyl group of L-His can coordinate with Cu2+ ions to form stable L-His–Cu2+ complexes, the color of the TMB-H2O2 solution remains unchanged after the addition of L-His. Therefore, because L-His effectively hinders the colorimetric reaction of TMB with H2O2, this assay can be used to quantitatively determine the concentration of L-His in samples. Under optimized conditions, our colorimetric sensor exhibited two linear ranges of 60 nM to 1M and 1M to 1 mM for L-His detection and a detection limit of 50 nM (S/N=3); furthermore, the assay can be performed within 20 minutes. Moreover, the proposed assay was used to determine the concentration of L-His in urine samples, suggesting that this convenient and label-free colorimetric method presents promising applications in bioanalytical chemistry and clinical diagnosis.